(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
Two key points of logarithm concept teaching design view are examined in this study. Present Reasons educational theory is examined for purpose of achieving profound understanding of subject content. Academic course subject content analysis is conducted to determine learning difficulties through investigating initial point of student cognition. Methods are then designed for bypassing study challenges from multiple levels and angles.